In the arena : a memoir of love, war, and politics - Robb, Charles S. (University of Virginia Press, 2021)
"The political memoir of Virginia governor and senator Chuck Robb. Covers his marriage to Lynda Bird Johnson, daughter of President Lyndon B. Johnson, his tour in Vietnam as a U.S. Marine, and his roles as lieutenant governor, then governor, and then US senator of Virginia"--